An emote opportunity model of computer abuse - Baskerville, Richard; Park, E.; Kim, J. (Emerald Group Publishing Limited, 2014)
Purpose – The purpose of this paper is to develop and evaluate an integrated computer abuse model that incorporates both organizational abuse settings and the psychological processes of the abuser. Design/methodology/approach – The paper developed an emote opportunity (EO) model through a comprehensive literature review and conducted a case study to evaluate the explanatory and prescriptive usefulness of the model. Findings – The EO model helps explain the interaction between organization-centric factors and individual-centric factors. It also helps explain how potential computer abusers elicit an emotion process component that ultimately contributes to computer abuse behaviors. The model connects both organizational external regulation processes and individual internal regulation processes to emote process components of potential abusers. Research limitations/implications – The study considers only organizational computing resources as the target of computer abuse. The model is evaluated by historical data from a computer abuse case. Future research with contemporary empirical data would further evaluate these findings. Organizations should be aware of the opportunities they create for abuse and the emotional state-of mind of potential abusers within organizations. Practical implications – Organizations should take a holistic approach that incorporates personal emotions and organizational abuse opportunity settings to prevent computer abuse. Originality/value – A multilevel, integrated EO model incorporating organizational environment and individual emotion processes provides an elaborated and holistic understanding of computer abuse. The model helps organizations consider the emotional state-of-mind of abusers as well as their organizational situation.